Paradigma Näkökulmia tieteen periaatteisiin ja käsityksiin - Hämäläinen, Niina; Kauppi, Petja (Kalevalaseuran vuosikirja, 2021)
The theme and title of the 100th Yearbook of the Kalevala Society is "Paradigm". Paradigm is a framework of prevalent principles, beliefs, values, and norms, and incorporates ideas about what is correct in terms of theory and methodology. Accordingly, paradigm always leads to struggles of authority in relation to other trends and ways of thinking. This book grapples with the historical, contemporary, and ever-shifting paradigms and methods of cultural research. What was being researched in the early 20th century and how was the research conducted? What happened in the 1960s-1980s in this field of research? What methods do our peers use? What kinds of affiliations and antagonisms emerge with the changing paradigms? And how do the different 'turns' direct research?